DIAGNOSIS OF TOXOPLASMOSIS IN ABORTIVE WOMEN AND STUDY OF SOME HEMATOLOGICAL AND IMMUNOLOGICAL PARAMETERS AMONG INFECTED PATIENTS IN WASIT PROVINCE - Zahraa Ali Faieq; Zainab Abbas Jasim Al-Maliki,; Russul Wassit Kadhum (Web of Journals Publishing, 2024)
The aim of study was detected of toxoplasmosis in Abortive Women and Study of some Hematological and Immunological Parameters among Infected Patients .120 blood samples were collected from aborted women (18- 40 years) whom attended to Al –kut Hospital for Gyneclogy and obstetrics and pediatrics. The results were revealed that 55(45.8%) positive for Toxoplasma antibodies. The higher infection rate was recorded in (25-30) years (40.0%) while the lower infection rate (9.09%) was recorded in age (36-40) years. The relation between infection with Toxoplasma and number of abortion has been studied, the results were showed that rate of one miscarriage in abortive women was 72.7% (40/55) higher than two and three miscarriages 23.6% (13/55) and 3.6% ( 2/55 ) respectively . The results showed high level of IL-10 and IL-17 in women with toxoplasmosis, which reached (290 ± 28.3 and 19 ± 2.4) pg/mL, respectively, compared to the control that reached (117 ± 11.8 and 9 ± 1.04) pg/mL, respectively. the result of Distribution of Patients According to Blood Groups Among the toxoplasmosis patients were the highest toxoplasmosis infection was found in the O blood group (43.7%), followed by A (31.2%), B (13.54%), and AB (11.45%). The mean levels of hemoglobin (10.4±3.8vs. 13.1±2.5 g/dL), red blood cell count (RBC 3.9*109±0.9 vs.4.4*109±0.9/μL), white blood cell count (WBC 11.2*109±1.9/L vs.6.7*109±1.8/L) and hematocrit (Hct 34.1±6.2 vs. 39.4±6.0 %) no significant variations were observed in mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and platelet count when comparing cases and controls for p-values > 0.05.
Keywords: Hematological , Immunological ,Toxoplasma gondii, Abortive Women.